1999
DOI: 10.1177/096368979900800114
|View full text |Cite
|
Sign up to set email alerts
|

Biocompatibility of Poly (DL-Lactide-co-Glycolide) Microspheres Implanted into the Brain

Abstract: The delivery of therapeutic molecules to the brain has been limited in part due to the presence of the blood-brain barrier. One potential solution is the implantation of biodegradable polymers with sustained release of drugs. Poly (DL-lactide-co-glycolide) (PLG) is a bioerodible polymer with a long and successful history of use as a suture material. More recently, PLG has been investigated for localized and sustained delivery of molecules into both peripheral sites and the brain. Despite its well-defined safet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
35
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(38 citation statements)
references
References 39 publications
3
35
0
Order By: Relevance
“…No evidence of damage was observed on the tissue that surrounds the implanted microparticles indicating that they were well tolerated. Consistent with previous reports, GFAP-positive reactive astrocytes were observed around the needle tract ( Figure 6A) [14,16,24]. This reaction was the same for the 3 groups of animals demonstrating that the astrocytic response is attributed to the mechanical trauma that occurs during surgery and not to the polymer.…”
Section: Histological Effects Of Striatal Gdnf Microparticle Implantasupporting
confidence: 91%
See 1 more Smart Citation
“…No evidence of damage was observed on the tissue that surrounds the implanted microparticles indicating that they were well tolerated. Consistent with previous reports, GFAP-positive reactive astrocytes were observed around the needle tract ( Figure 6A) [14,16,24]. This reaction was the same for the 3 groups of animals demonstrating that the astrocytic response is attributed to the mechanical trauma that occurs during surgery and not to the polymer.…”
Section: Histological Effects Of Striatal Gdnf Microparticle Implantasupporting
confidence: 91%
“…First of all, microparticles are prepared with biodegradable polymers that do not require removal once the treatment is finished. Secondly, brain biocompatibility of particles prepared with poly (lactic-co-glycolic) acid (PLGA) polymers has already been well established [13][14][15][16] and therefore the appearance of host immune reaction against injected microparticles is very unlikely. Finally, the drug release profile of PLGA microspheres brings another important advantage.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that the CNS tissue response to PLGA drug carriers is a moderate and non-specific inflammatory reaction due to the mechanical trauma by implantation, irrespective of the drug carrier shape or the implantation site (Menei et al 1993;Lillehei et al 1996, Kou et al 1997Emerich et al 1999;Fournier et al 2003). Local injection of PLGA microspheres has been used to deliver anti-tumour agents such as mitoxantrone, hemopexin, platelet factor 4 fragment, 5-fluoro-uracil and carboplatin (Menei et al 1996;Chen, W. et al 1997;Benny et al 2005;Yemisci et al 2006) for treatment of brain tumours.…”
Section: Local Delivery Systemsmentioning
confidence: 99%
“…48,51 Generally considered as biocompatible, 41 PLA or PLGA microspheres have also a good CNS biocompatibility. 52,53 No mortality was reported with albumin-coated nanoparticles in mice with up to a 2000 mg/kg dose. 44 However, PLA 60000 nanoparticles stabilized with sodium cholate were much more toxic with two of five deaths at a 220 mg/kg dose and five of five at a 440 mg/kg dose associated with marked clinical signs (dyspnea, reduced locomotor activity), alteration of hematological and biochemical parameters and lung hemorrhage.…”
Section: General Considerationsmentioning
confidence: 99%